The Hadaf and Tsaqafah al-Mufassir: Analysis of the Aims and Background in Writing the Qur'an - Hasanah, Mumun Munawarotul; Almunawar, Nursaid Agil (UIN Sunan Gunung Djati Bandung, 2026)
In writing an exegetical text (tafsir), a Qur'an commentator (mufassir) cannot be separated from their tendencies and ideology. Therefore, as a reader of tafsir, it is necessary to know the mufassir's goal (hadaf) and background (tsaqafah al-mufassir) to obtain an authentic interpretation result, untainted by group interests. The objective of this research is to examine the hadaf tafsir (goal of exegesis) and tsaqafah al-mufassir (cultural/intellectual background of the mufassir) and their connection to the interpretive goal and the background of the tafsir book's writing. The research method for this study is qualitative with a descriptive-analytic approach. Data collection is carried out through a literature review. The results of this study indicate that hadaf tafsir refers to the core objective or desire that a mufassir aims to achieve in interpreting the verses of the Qur'an. Meanwhile, tsaqafah (background/culture) is the context that accompanies the mufassir, shaping their scientific insight, socio-cultural environment, and environmental influences, which ultimately impact the formation of their character and personality. By knowing these two things, readers can evaluate the work of tafsir more critically. Efforts to determine the hadaf tafsir can be seen in biographical elements, including family background, educational history, and life history, as well as the author's psychological, social factors, and life philosophy. The mufassir's background influences the choice of methodology and interpretive style (corak tafsir) adopted. This is because the methodology affects how the mufassir conveys the goal of the interpretation. Meanwhile, the interpretive style can be seen from the dominant tendency in the tafsir book.